An environment friendly free-standing cellulose membrane derived for catalytic reduction of 4-nitrophenol: A sustainable approach. Issue 1 (February 2021) - Das, Tushar Kanti; Remanan, Sanjay; Ghosh, Sabyasachi; Das, Narayan Ch.
Graphical abstract: Facile preparation of a biodegradable cellulose derived free-standing high water flux catalytic nanocomposite membrane through mussel inspired polymer chemistry for gravimetric catalytic conversion of toxic 4-Nitrophenol (4-NP). Highlights: In-situ synthesized AgNPs decorated nanocellulose (NC) based free standing membrane was fabricated by economical facile vacuum filtration method. The fabricated AgNPs@NC membranes shows high water flux compared to that of pure NC membrane under gravimetric flow. The membranes also shows excellent catalytic activity towards the conversion of hazardous 4-nitrophenol in batch reactor as well as under gravimetric flow. High water permeability as well as improved catalytic reduction observed when modified membranes were stacked together. Abstract: Catalytic active and high flux free standing cellulose membrane is developed through mussel inspired polydopamine (PDA) chemistry using facile vacuum filtration method. Herein, quasi-spherical silver nanoparticles (AgNPs) illuminated nanocelluose (NC) fiber (AgNPs@NC) based membrane was fabricated by in-situ reduction of silver salt over the surface of nanometer thick PDA coated synthesized NC. The permeation behavior of the membranes was studied using pure water under gravimetric condition. The catalytic activity was evaluated by assessing the reduction of 4-nitrophenol (4-NP) as a water contaminant. The conversion efficiency of the 4-NP by the stacking membranes under gravimetric condition showed above 95 %. The catalytic activity was also studied toward reduction of 4-NP in a batch reactor and complete conversion could be accomplished within 8 min having turn over frequency (TOF) 2.25 × 10 −3 molecules per gram per min. High water flux of the fabricated membrane was possibly due to the hydrophilicity of the PDA coated NC and hydrophobic pushing of AgNPs. Excellent catalytic activity of the synthesized AgNPs@NC membrane can be described by the synergistic effect of PDA coated NC and AgNPs. Beside this, higher number of catalytic reusability proved excellent bonding ability of adhesive like PDA between NC and AgNPs. In future, the fabricated AgNPs@NC membrane would be a potential candidate as catalytic converter for industrial applications.